The Exit Strategy Process in the Corporate Social Responsibility Program: A Case Study of the Kampung Berseka Program by PT Bio Farma (Persero) - Risna Resnawaty; Wandi Adiansah; Tendry Firmansyah; Hidayat Setiadji (International Journal of Business, Economics, and Social Development, 2026)
Corporate Social Responsibility (CSR) practice is a form of corporate commitment to supporting sustainable social and environmental development. The success of CSR based on community development is not only determined by the achievements of the program, but also by the existence of an exit strategy that is able to encourage community independence and sustainability. This study aims to analyze the implementation of exit strategy in the BERSEKA Village Program implemented by PT Bio Farma (Persero) in Padaasih Village, Conggeang District, Sumedang Regency. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews with PT Bio Farma (Persero) who are directly involved in the formulation and implementation of the program, and supported by a documentation study consisting of program implementation reports, social mapping results, and monitoring and evaluation documents owned by PT Bio Farma (Persero). The results of the study show that the exit strategy in the BERSEKA Village Program is designed gradually and systematically through the phasing down, phasing out, and phasing over mechanisms. This strategy is realized through gradual reduction of the role of companies, strengthening local capacity and institutions, and transferring management roles to the community and village government. The implementation of the exit strategy contributes to maintaining the sustainability of the program and reducing the community's dependence on external interventions.